Significance of serum and pathological biomarkers in fertility-sparing treatment for endometrial cancer or atypical hyperplasia: a retrospective cohort study - Yiqin Wang; Rong Zhou; Xiaobo Zhang; Huixin Liu; Danhua Shen; Jianliu Wang (BMC, 2021)
Abstract Background This study analyzed the changes of serum and pathological biomarkers during fertility-sparing therapy of endometrial cancer (EC) or endometrial atypical hyperplasia (EAH), to investigate their implications for early prediction of treatment efficacy. Methods A retrospective analysis of EC or EAH patients who received fertility-sparing therapy between 2012 and 2016 was performed. Serum and endometrium sampling were obtained for each patient at three time points: at baseline, at 3-6 months' treatment and at the end of conservative treatment. Serum biomarkers including insulin resistance (HbA1c, HOMA-IR), sex hormones and thyroid hormones were measured. Meanwhile expression of endometrial pathological biomarkers including ER, PR, PRB and Ki-67 was also assessed by immunohistochemistry. Results For the 53 recruited patients, overall complete response, recurrence and pregnancy rates were 94%, 26% and 36.4%. During the treatment, the serum biomarkers of HOMA-IR remained stable, while pathological markers including PR, PRB and Ki67 diminished significantly. Patients who achieved remission faster had significant lower HOMA-IR level and higher PRB expression at baseline. We also found a more remarkable down-regulation of PRB related with faster remission. Further multivariate analysis confirmed that baseline HOMA-IR ≥ 2.5 negatively affected treatment time to remission (OR 0.206; p = 0.017). While marked reduction of PRB (≥ 30%) at 3-6 months' treatment correlated with faster remission (OR 5.788; p = 0.010). Conclusion For EC and EAH patients who received fertility-sparing therapy, baseline status of insulin resistance predicted poor response to progestin, while marked reduction of PRB following the initial 3-6 months' treatment predicted fast remission.